The determinants of financial inclusion in the Khomas and Oshana Region, Namibia - Iyambo, Tupa-Omukumo (My University, 2020)
Financial inclusion for all segments of society is a key factor that helps improve the quality of life experienced by marginalised groups. Financial inclusion entails access to a wide range of affordable and accessible financial products that cater to various socio-economic realities. Financial inclusion is affected by a myriad of factors that are categorised by supply-side and demand-side factors. The supply-side factors focus on the supply of financial services from financial institutions ,these factors fail to grasp the various socio-economic contexts attached to the issue of financial inclusion. The demand-side factors focus on socio-economic factors such as age, education and income when measuring financial inclusion. These factors provide a clearer image of the socio-economic contexts related to financial inclusion. Financial inclusion is a key factor in tackling urban planning issues such as reducing poverty and economic development specifically in developing countries. Financial inclusion is highlighted in one of the main agendas as a catalyst for inclusive economic growth in the Namibian Financial Sector Strategy. Financial exclusion in Namibia is an issue predominantly experienced by marginalised groups in the country, which encompass low-income groups and individuals in rural areas. The introduction of mobile money initiatives such as the Mobi-pay mobile money scheme has significantly helped reduce the intensity of financial exclusion in Namibia. Although initiatives were launched to curb this issue ,the various socio-economic contexts that exist in all 14 regions of Namibia make it difficult to provide safe and affordable financial products to all segments of society. This research aims at identifying the pertinent factors of financial inclusion guided by theory that focuses on various studies related to financial inclusion. An exploratory case study quantitative research method will be undertaken in this paper, where a binary logistic regression model will make use of the data from the 2017 Namibian Financial Inclusion survey compiled by the Namibian statistics agency. The results from the financial inclusion model show that the urban/rural dichotomy, income level, education level, ownership of a bank account , savings capability , borrowing money, age and distance from the bank as significant factors in the Khomas region compared to the Oshana region which identified education level and tenure status as significant. The education level is the only common factor shared between the two regions , which highlights that the education level is the most pertinent factor of financial inclusion. The study concludes that the aforementioned factors in both regions are significant and need to be focused on when improving the state of financial inclusion in Namibia , with a particular focus on financial literacy
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Development Planning, 2020